Trajectory Optimization of Lower Extremity Rehabilitation Robots Based on Cycloid - Cui Bingyan; Zeng Hongtai; Yang Zhongyuan; Gui Xiaogeng; Li He; Wang Jingwei (Jixie chuandong)
With the rapid development of modern robotics and medical industry, the use of rehabilitation robots for the treatment of patients with lower limb sports injuries has become one of the research hotspots at home and abroad. In order to achieve better rehabilitation treatment effect, trajectory planning of a three-degree-of-freedom lower limb rehabilitation robot is studied, and the motion law of healthy ankle joint is simulated to optimize the trajectory design of the lower limb rehabilitation robot. Based on the rehabilitation, injury mechanism, and motion form of the ankle joint, a comparative analysis of several low degree of freedom planar symmetric parallel mechanisms is conducted, and a design prototype using a 2UU-UPU mechanism as the rehabilitation actuator is determined; research on trajectory planning for lower limb rehabilitation training of lower limb rehabilitation robots, trajectory planning motion formulas for cycloidal motion laws and superimposed cycloidal motion laws are derived, and the rationality of trajectory under different rehabilitation training conditions is verified. In order to further explore a more reasonable rehabilitation trajectory, the optical motion capture system is used to collect the ankle joint movement trajectory in the sitting position, establish the rehabilitation trajectory constraints, improve the similarity between the planned trajectory and the human movement, and achieve better rehabilitation effect.